Engineering Materials 2 - Bolton, William (Newnes, 2013)
Engineering Materials 2 covers an introduction to the properties and structures of engineering materials. The book discusses the types of factors determining the choice of a material; the main properties required of engineering materials; the main methods used for tensile testing, impact testing, bend tests, and hardness measurements and the interpretation of measurements; and the interpretation of thermal conductivity and electrical conductivity data. The text also describes the basic structure of materials; the effect of hot and cold work on a metal structure; and the effect of grain size and shape on the mechanical properties of metals. The basic structural features of thermoplastic, thermosetting, and elastomer materials, relating the mechanical and thermal properties to the structures, and the properties of common plastics, relating the properties to their structures, are also described. The book tackles the main categories of polymer forming and their products; the mechanical properties of composites and the properties of the matrix and fiber; and the environmental stability of materials. Engineering students and technicians will find the book invaluable.